Topological analysis of DPY19L3, a human C‐mannosyltransferase. (16th February 2018) - Niwa, Yuki; Nakano, Yoshihiko; Suzuki, Takehiro; Yamagishi, Mizuo; Otani, Kei; Dohmae, Naoshi; Simizu, Siro
Abstract : C ‐mannosylation is a rare type of protein glycosylation, the functions and mechanisms of which remain unclear. Recently, we identified DPY19L3 as a C ‐mannosyltransferase of R‐spondin1 in human cells. DPY19L3 is predicted to be a multipass transmembrane protein that localizes to the endoplasmic reticulum (ER); however, its structure is undetermined. In this study, we propose a topological structure of DPY19L3 by in silico analysis and experimental methods such as redox‐sensitive luciferase assay and introduction of N ‐glycosylation sites, suggesting that DPY19L3 comprises 11 transmembrane regions and two re‐entrant loops with the N‐ and C‐terminal ends facing the cytoplasm and ER lumen, respectively. Furthermore, DPY19L3 has four predicted N ‐glycosylation sites, and we have demonstrated that DPY19L3 is N ‐glycosylated at Asn 118 and Asn 704 but not Asn 319 and Asn 439, supporting our topological model. By mass spectrometry, we measured the C ‐mannosyltransferase activity of N ‐glycosylation‐defective mutants of DPY19L3 and isoform2, a splice variant, which lacks the C‐terminal luminal region of DPY19L3. Isoform2 does not possess C ‐mannosyltransferase activity, indicating the importance of the C‐terminal region; however, N ‐glycosylations of DPY19L3 do not have any roles for its enzymatic activity. These novel findings on DPY19L3 provide important insights into the mechanism of C ‐mannosylation. Abstract : We here propose the topological model of DPY19L3, a human C ‐mannosyltransferase. DPY19L3 comprises 11 transmembrane regions and two re‐entrant loops with the N‐ and C‐terminal ends facing the cytoplasm and endoplasmic reticulum lumen, respectively, and has two N ‐glycosylation sites. Furthermore, we also propose the essential region for C ‐mannosyltransferase activity, which is the C‐terminal luminal region of DPY19L3.